Nigeria : 2016 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses outlook and risk for Nigeria. Its economy has been hit hard by global developments that have aggravated longstanding development weaknesses. Macrofinancial outcomes are closely linked with the price of oil. Policy uncertainty has amplified the impact of global developments. The large permanent terms-of-trade shock requires a significant macroeconomic adjustment. It is important to initiate urgently an integrated package of policies centered on a fundamental change in the nature of government; reducing external imbalances (including real exchange rate realignment); further safeguarding the resilience and improving the efficiency of the banking sector; and implementing structural reforms for inclusive growth.